E-Learning Media Based on Verbal-Visual Interpersonal Intelligences on Speaking Skills in PBSI UTM - Dwi Farisa A; Miftahul Ummah E; Seli Dewi S; Afiyah Nur K; Siti Mutiatun (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
This research focused on online learning. This is expected on student’s multiple Intelligence based, especially in verbal linguistic, visual spatial, and interpersonal intelligence. The steps of this research consisted of searching and finding problems, initiate an idea, and taking data through filling out online questionnaires by student and lecturer. This research shows that the development of student's multiple intelligences are not run optimally when they got online learning. Practicality and effectiveness of learning assessed in the intermediate category, this is evidenced in the student’s responses of filling out online questionnaire. This research will initiate an idea for learning media that based on multiple intelligences on speaking skill, and is expected to succeed in maximizing of student’s understanding. Thus, online learning can run effectively and efficiently as like offline learning.